Risk of Gastrointestinal Bleeding in Patients with End-Stage Renal Disease: The Link between Gut, Heart, and Kidneys - Avleen Kaur; Syed M. Baqir; Kundan Jana; Kalyana C. Janga (Gastroenterology Research and Practice)
Patients with end-stage renal disease (ESRD) have a five times higher risk of gastrointestinal bleed (GIB) and mortality than the general population. Aortic stenosis (AS) has been associated with GIB from intestinal angiodysplasia. In this retrospective analysis, we obtained data from the 2012 and 2019 National Inpatient Sample. The primary outcome of interest was all-cause in-hospital mortality and risk factors of mortality in patients with ESRD with GIB with aortic valve disorders especially AS. We identified all patients (≥18 years of age) with ESRD (n=1,707,452) and analyzed based on discharge diagnosis of valvular heart disease (n=6521) in patients with GIB compared with those without GIB (n=116,560). Survey statistical methods accounting for strata and weighted data were used for analysis using survey packages in R (version 4.0). Baseline categorical data were compared using Rao-Scott chi square test, and continuous data were compared using Student’s t-test. Covariates were assessed using univariate regression analysis, and factors with p value less than 0.1 in the univariate analysis were entered in the final model. The univariate and multivariable associations of presumed risk factors of mortality in ESRD with GIB patients were performed by Cox proportional hazards model censored at length of stay. Propensity score matching was done using MatchIt package in R (version 4.3.0). 1 : 1 nearest neighbour matching was done with propensity scores estimated through logistic regression, in which occurrence of GIB, valvular lesions, and AS was regressed according to other patient characteristics. Among patients with ESRD with valvular heart diseases, AS was found to be associated with increased risk of GIB (adj.OR=1.005; 95% CI 1.003–1.008; p<0.01). ESRD patients with AS showed increased risk of lower GIB (OR=1.04; 95% CI 1.01–1.06; p=0.02), colonic angiodysplasia (OR=1.03; 95% CI 1.01–1.05; p<0.01), stomach and duodenal angiodysplasia (OR=1.03; 95% CI 1.02–1.06; p<0.01), need for blood transfusion add pressors as compared to those without AS. However, there was no increased risk of mortality (OR=0.97; 95% CI 0.95–0.99; p<0.01).